"They hate pigs, Chinese farmers ... everything!" Beastly Racialization in Multiethnic Malaysia - Neo, Harvey (Antipode, 2012)
:  This paper details the construction of the pig and the pig industry in Malaysia. It argues that a pattern of “animal‐linked racialization” continually polices the boundary between the dominant, elite Malay‐Muslim hegemony and the comparatively less powerful Chinese pig farmers. Often subtle and implicit, such beastly racialization, drawing frequently from religious and nationalist tropes, renders visible the taboo subjects of race and racism in Malaysia. While a simplistic form of beastly racialization in relation to the pig industry is held by the political elites and non‐Chinese community, one cannot say that such a racialization has produced or sustained distinct racisms. Nonetheless, it is through the process of beastly racialization that we unravel the seemingly random acts of coercive policies that, taken in their entirety, threaten to stymie the future viability of the industry and continue to accentuate the visible social‐cultural disjuncture between the two biggest ethnic groups in Malaysia.